Cortisol Awakening Response as a Prospective Risk Factor for Depressive Symptoms in Women After Treatment for Breast Cancer. Issue 7 (September 2017) - Kuhlman, Kate Ryan; Irwin, Michael R.; Ganz, Patricia A.; Crespi, Catherine M.; Petersen, Laura; Asher, Arash; Bower, Julienne E.
ABSTRACT: Objective: The aim of the study was to investigate hypothalamic-pituitary-adrenal axis (HPA axis) functioning as a neurobiological risk factor for depressive symptoms in an ongoing longitudinal, observational study of women undergoing treatment and recovery from breast cancer. Many women with breast cancer experience depressive symptoms that interfere with their treatment, recovery, and quality of life. Psychosocial risk factors for depression among patients with cancer and survivors have been identified, yet neurobiological risk factors in this population remain largely unexamined. Methods: Women recently diagnosed with early-stage breast cancer ( N = 135) were enrolled before starting neoadjuvant/adjuvant treatment (radiation, chemotherapy, endocrine therapy). At baseline, participants collected saliva samples to measure diurnal HPA axis functioning for 3 days: at waking, 30 minutes after waking, 8 hours after waking, and bedtime. Participants also completed a standardized measure of depressive symptoms (Center for Epidemiological Studies-Depression Scale) at baseline and 6 months after completion of primary treatment. Multivariate regression was used to predict continuous depressive symptoms at 6-month posttreatment from continuous depressive symptoms at baseline, cortisol awakening response (CAR), and other measures of diurnal HPA axis functioning. Results: The magnitude of CAR predicted changes in depressive symptoms over time, such that women with a higher CAR showed a greater increase from baseline to 6-month posttreatment ( b = 5.67, p = .023). Diurnal slope and total cortisol output were not associated with concurrent depressive symptoms or their change over time. Conclusions: Elevated CAR may be a neurobiological risk factor for increases in depressive symptoms in the months after breast cancer treatment and warrants further investigation.